2011
DOI: 10.1038/nbt.1932
|View full text |Cite
|
Sign up to set email alerts
|

The genomic sequence of the Chinese hamster ovary (CHO)-K1 cell line

Abstract: Therapeutic proteins and antibodies represent a $125 billion annual market. Chinese Hamster Ovary (CHO) derived cell lines are the preferred host cells for the production of therapeutic proteins. Here, we present a draft genomic sequence of the CHO-K1 ancestral cell line. The assembly comprises 2.45Gb genomic sequence with 24,383 predicted genes. We associate most scaffolds to 21 microfluidically-isolated chromosomes to identify chromosomal locations of genes. Furthermore, we investigate genes involved in glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
612
1
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 713 publications
(633 citation statements)
references
References 51 publications
12
612
1
8
Order By: Relevance
“…In addition, for >30 years, they have been the host cell of choice for production of most biotherapeutics. While the aforementioned research was carried out without genomic resources, new opportunities are arising with published CHO genome sequences [Xu et al, 2011], [Brinkrolf et al, 2013], [Lewis et al, 2013], [Yusufi et al, 2017]. However, the draft nature of these genome sequences pose challenges for many applications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for >30 years, they have been the host cell of choice for production of most biotherapeutics. While the aforementioned research was carried out without genomic resources, new opportunities are arising with published CHO genome sequences [Xu et al, 2011], [Brinkrolf et al, 2013], [Lewis et al, 2013], [Yusufi et al, 2017]. However, the draft nature of these genome sequences pose challenges for many applications.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry analyses demonstrated the complete lack of core fucose on N -glycans attached to the EPO-Fc fusion protein and IgG1 antibodies produced in the CHO-gmt3 cells 80 . The CHO-K1 transcriptome data have shown that among all Golgi fucosyltransferases, only FUT8 is expressed 82 . Therefore, inactivating Fut8 or Slc35c1 should have similar effects on CHO-K1 cells.…”
Section: Strategies To Produce Afucosylated Antibodiesmentioning
confidence: 99%
“…2). The final gene set consisted of 24,044 genes in the hamster genome, which is similar to that of the CHO-K1 cell line 5 . Of these predicted genes, 23,473 clustered into 21,628 gene families (Fig.…”
Section: Genome Annotationmentioning
confidence: 99%
“…Meanwhile, efforts to engineer mouse cells have greatly benefited from numerous genomic tools and technologies, owing in large part to the availability of the Mus musculus reference genome sequence. Genomic resources are also becoming available for CHO cells, such as the CHO-K1 genome 5 , expressed sequence tag 6,7 and bacterial artificial chromosome (BAC) libraries 8 , and compendia of proteomic [9][10][11] and transcriptomic data 7,[12][13][14][15][16] . However, much like how murine cell line data are routinely studied in the context of the Mus musculus reference genome, there is a need for a standard reference for all CHO cell lines to contextualize all of these valuable genomic resources.…”
mentioning
confidence: 99%